Publisher's Comment. The Ethnocide Of The Other Is Also Our Own Death. - Mojica Mendieta, Francisco Javier (2020)
This editorial raises the problem of the ethnocide of the Other as the modus operandi equivalent to murder-suicide against humanity itself. To this end, it problematizes the murders in Costa Rica of Yeri Rivera Rivera, the Bröran indigenous leader of Térraba, on February 24, 2020, and Sergio Rojas Ortiz, the Bribri indigenous leader, on March 18, 2019, in the process of recovering their territories from non-indigenous usurpers and their allies. Methodologically, an ethnographic approach was carried out with open interviews to achieve a dialogical approach with his comrades in struggle. The analysis allows us to conclude that both murders have a deep root of racism in Costa Rica and other countries of the Global South; they target the forced disappearance of indigenous leaders and social activists; they are part of internal colonialism; they commit the ethnocide of the Other, which is also our own death and, like so many other murders, remain unpunished. As part of our commitment from the public university, Trama, the Social Sciences and Humanities Journal, in the face of these facts, positions itself as a space for the communication of knowledge that liberates from racism, xenophobia, patriarchy, capitalism and colonialism. Keywords: colonality; emancipation; humanism; social struggle